A Survey on Finger Knuckle Print based Biometric Authentication - Sathiya, L; Palanisamy, V (International Journal of Computer Sciences and Engineering, 2018)
Nowadays biometrics based authentication could be a one amongst the necessary technology during this world. Authentication means whether that person is genuine or not. Based on this authentication so many physical and behavioural characteristics are used. Physical characteristics are face, fingerprint, iris, retina, palm print, finger vein and finger knuckle print and behavioural characteristics means that basic actions done by the person like voice, giant, ECG, EEG, keystroke, handwriting and lip movements. Based on this physical traits finger knuckle print is one of the most interest research arena of the researchers nowadays. Because it can be easily accessed, low cost devices are used to capture the image; it cannot be stolen by others, etc. In finger knuckle print based authentication we have got to survive such a lot of papers. Per this study the finger knuckle print encompasses a heap of deserves and limitations. To provide a comprehensive survey, this paper presents a summary of finger knuckle print biometric system, their applications and limitations.